Pengaruh pola asuh orang tua pada anak usia Golden Age: Menentukan karakter pada anak - Priskova, Putri Dwi (Maliki Interdisciplinary Journal, 2024)
Parents are the first important role in the pattern of parenting which has a very large influence on the formation of children’s character. There is one important phase that parents should not miss in paying attention to the growth and development of their children so that unwanted character formation does not occur, this phase is called the golden age phase. This research was conducted to provide new insights regarding the importance of good parenting, especially during the golden age period, so that good character is formed in children. The implementation of this research will use a qualitative method using data collection techniques in the form of a literature review. The results of the study showed that there was a significant influence between the parenting style of the golden age children’s parents on the child’s character. The better the parenting style given to the child by the parents, the better the impact on the character of the child itself.